Effect of Human Bone Marrow Mesenchymal Stem Cells on Burn Healing in Granulation Tissue Formation in Diabetic Rats - Revilla, Gusti; Saputra, Deddy; Nurhasanah, Dini (Faculty of Medicine, Universitas Andalas, 2022)
Burns with diabetes mellitus can interfere with the wound-healing process. Mesenchymal stem cells have been studied to accelerate the healing of burns, one of which originates from the bone marrow. Objective: To determined the effect of human bone marrow mesenchymal stem cells (hBM-MSCs) on burn wound healing in granulation tissue formation in Diabetes Mellitus rats. Methods: This study was an experimental study with a post-test-only control group design, using 30 rats divided into two groups, the control group Phosphate Buffer Saline (PBS) and the treatment group (hBM-MSCs). Mice were induced by alloxan to cause hyperglycemia. Burns are made using a heated plate. Tissue collection was carried out after the termination of the experimental animals on the 3rd, 7th and 14th days and then histological preparations were made to assess the formation of granulation tissue. Data were analyzed using the two-way ANOVA test. Results: There was an increase in the number of macrophages, fibroblasts and new blood vessels after being given hBM-MSCs. On day 14 neutrophils and lymphocytes on day 3, there was no increase. Statistical analysis showed a significant increase in lymphocytes, macrophages, fibroblasts and new blood vessels. Conclusion: Human bone marrow mesenchymal stem cells can increase the formation of granulation tissue by increasing the number of macrophages, fibroblasts and new blood vessels in diabetic rats.Keywords: burn wound, Â diabetic rat, human bone marrow mesenchymal stem cells, granulation tissue